2016
DOI: 10.1016/j.biomaterials.2016.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Guided bone regeneration is promoted by the molecular events in the membrane compartment

Abstract: The working hypothesis of guided bone regeneration (GBR) is that the membrane physically excludes non-osteogenic tissues from interfering with bone healing. However, the underlying mechanisms are insufficiently explained. This study aimed to investigate the molecular and structural pattern of bone healing in trabecular bone defects, with and without naturally derived resorbable membrane. Defects were created in rat femurs and treated with the membrane or left empty (sham). After 3d, 6d and 28d, the defect site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
149
4
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(168 citation statements)
references
References 83 publications
12
149
4
3
Order By: Relevance
“…Consistent with the aforementioned findings on non‐resorbable, synthetic, PTFE membrane, it has been recently demonstrated that the presence of resorbable, naturally derived, collagen membrane promotes coupled increase in bone formation and bone‐remodeling genes (osteocalcin, calcitonin receptor, cathepsin K, and RANKL) in the underlying rat tibia defect, compared with a similar defect without membrane (Fig. ).…”
Section: Biological Mechanisms Of Gbrsupporting
confidence: 79%
See 1 more Smart Citation
“…Consistent with the aforementioned findings on non‐resorbable, synthetic, PTFE membrane, it has been recently demonstrated that the presence of resorbable, naturally derived, collagen membrane promotes coupled increase in bone formation and bone‐remodeling genes (osteocalcin, calcitonin receptor, cathepsin K, and RANKL) in the underlying rat tibia defect, compared with a similar defect without membrane (Fig. ).…”
Section: Biological Mechanisms Of Gbrsupporting
confidence: 79%
“…Interestingly, the latter observation was associated with greater transmembrane vascularization and membrane degradation . Additional support for a role of multinucleated cells during GBR is the observation of these cells particularly in the zone between the lower surface of the membrane and the upper surface of the newly formed bone . At the histological level, these multinucleated osteoclast‐like cells appeared to be in a process of active resorption of the underlying bone, but it was not possible to determine whether these cells were also involved in the process of membrane degradation .…”
Section: Biological Mechanisms Of Gbrmentioning
confidence: 99%
“…Because the first generation of GBR membranes was used in the clinic, ePTFE membranes have generally shown satisfactory results with respect to both their biocompatibility and the positive maintenance of spaces during healing. However, a second surgical operation is required to remove the ePTFE membrane, which may increase patient morbidity, the economic burden, and infection and may potentially damage the newly regenerated tissues (Ghanaati, ; Ma et al, ; Turri et al, ). To overcome the above drawbacks, bioresorbable barrier membranes as the second generation of GBR membranes have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…As observed with non‐resorbable PTFE membranes, naturally derived, resorbable, collagen membranes promote an early coupled upregulation of genes related to bone formation (OC) and bone remodelling (the calcitonin receptor (CTR), cathepsin K (CatK) and RANKL)) in the underlying defect compared to the expression of these genes in the untreated sham defect in the rat femur (Turri et al., ; Figure ). Further, the presence of a collagen membrane above the defect appeared to fine‐tune the expression of the pro‐inflammatory cytokine tumour necrosis factor alpha (TNF‐α) during the different phases of GBR, as indicated by the early peak of TNF‐α at day 3 followed by significant downregulation at day 6 and a second peak at day 28 in the defect treated with the collagen membrane (Turri et al., ).…”
Section: Results Of the Literature Surveymentioning
confidence: 92%
“…As observed with non‐resorbable PTFE membranes, naturally derived, resorbable, collagen membranes promote an early coupled upregulation of genes related to bone formation (OC) and bone remodelling (the calcitonin receptor (CTR), cathepsin K (CatK) and RANKL)) in the underlying defect compared to the expression of these genes in the untreated sham defect in the rat femur (Turri et al., ; Figure ). Further, the presence of a collagen membrane above the defect appeared to fine‐tune the expression of the pro‐inflammatory cytokine tumour necrosis factor alpha (TNF‐α) during the different phases of GBR, as indicated by the early peak of TNF‐α at day 3 followed by significant downregulation at day 6 and a second peak at day 28 in the defect treated with the collagen membrane (Turri et al., ). Despite the controversy regarding the role of inflammation and pro‐inflammatory cytokines during bone healing, TNF‐α is crucial for intra‐membranous bone formation (Gerstenfeld et al., ), and the observed early increase in TNF‐α expression in the membrane‐treated defect may positively impact the recruitment of cells, including mesenchymal stem cells (MSCs) (Bocker et al., ; Fu et al., ), and the osteogenic differentiation of these cells (Hess, Ushmorov, Fiedler, Brenner, & Wirth, ).…”
Section: Results Of the Literature Surveymentioning
confidence: 92%